Differentiation of parents' moral cultivation in educating children in the South Sulawesi - Afiah, Nur (Journal of Advanced Guidance and Counseling, 2024)
Purpose -  The research conducted aims to complement previous research on differences in moral cultivation carried out by parents in educating children. Method - This quantitative research was conducted to examine differences in parents' moral instilling in educating children in four regions in South Sulawesi, namely Parepare, Barru, Sidrap, and Pinrang. The research subjects were 133 parents who had children between the ages of 6 and 12 years. Results - The results showed that there were differences in the moral inculcation of parents in educating children in the South Sulawesi region with statistical similarities, namely (Sig) < 0.05 or (0.003) < 0.05. Implication - The research conducted recommends that parents be provided with pills or carry out psychoeducation regarding moral values and parenting. This aims to prepare a superior generation who is able to compete and be accepted in society amidst the increasingly rapid development of science and technology. Originality/Value - There are differences in the cultivation of morals carried out by parents in educating children in the South Sulawesi region. This is in line with research conducted by Children learn about right and wrong things from parents. The family atmosphere and the way of disciplining children are factors that play an important role. *** Tujuan - Penelitian yang dilakukan bertujuan untuk melengkapi penelitian sebelumnya mengenai perbedaan penanaman moral yang dilakukan orang tua dalam mendidik anak. Metode - Penelitian kuantitatif ini dilakukan untuk menguji perbedaan penanaman moral orang tua dalam mendidik anak di empat daerah di Sulawesi Selatan, yaitu Parepare, Barru, Sidrap, dan Pinrang. Subjek penelitian adalah 133 orang tua yang memiliki anak berusia antara 6 dan 12 tahun. Hasil - Hasil penelitian menunjukkan bahwa terdapat perbedaan penanaman moral orang tua dalam mendidik anak di wilayah Sulawesi Selatan dengan kesamaan secara statistik, yaitu (Sig) < 0,05 atau (0,003) < 0,05. Implikasi - Penelitian yang dilakukan merekomendasikan agar para orang tua dibekali dengan pil atau melakukan psikoedukasi mengenai nilai-nilai moral dan pola asuh anak. Hal ini bertujuan untuk mempersiapkan generasi unggul yang mampu bersaing dan diterima di masyarakat di tengah perkembangan ilmu pengetahuan dan teknologi yang semakin pesat. Orisinalitas/Nilai - Terdapat perbedaan penanaman moral yang dilakukan oleh orang tua dalam mendidik anak di wilayah Sulawesi Selatan. Hal ini sejalan dengan penelitian yang dilakukan oleh Anak belajar tentang hal yang benar dan salah dari orang tua. Suasana keluarga dan cara mendisiplinkan anak menjadi faktor yang berperan penting.